Mezi folklorem a uměním, mezi zeměmi a existencí - Pavera, Libor (Slavia Centralis, 2020)
Between folklore and art, between countries and existence The author deals with a writer who lived and wrote on a geographical borderline, as well as on linguistic and cultural borderlines, which is reflected in her work. It is placed between artistic literature and folklore. The author also considers several special motifs, e.g., the use of exemplum, time and space and the topic of place.